Contribution of participation and resilience to quality of life among persons living with stroke in Sweden: a qualitative study - Marie Matérne; Grahame Simpson; Gustav Jarl; Peter Appelros; Mialinn Arvidsson-Lindvall (International Journal of Qualitative Studies on Health & Well-Being, 2022)
Purpose Resilience contributes to positive adaptation after many health conditions, but little is known about its contribution to long-term recovery after stroke. This study investigated the lived experience of resilience and participation and their relationship to quality of life after stroke in Sweden. Material and method Semi-structured telephone interviews were conducted with 19 informants (10 male, 9 female), aged from 44–89 years and between 1 and 19 years post-stroke. Stroke severity ranged from mild (n = 8), moderate (n = 9) to severe (n = 2). Interviews were analysed using content analysis. Results The analysis resulted in an overarching theme; Life with stroke has been adapted to but not accepted, built on five subthemes: 1) Adapting and adjusting life, 2) Meaningful values in life, 3) Inner resources, 4) Support and treatment from social relations, and 5) Support and treatment from external resources. Conclusion Participants described a tension between adapting and accepting life after stroke. Resilience was a useful framework, highlighting the contribution of inner, social and societal resources to recovery and quality of life, both directly and as enhanced through increased participation. Important factors for adaptation are meaningful values in life, individual strategies for adaptation and support from both social relationship and the society.